ANALISIS FIRM VALUE PADA PERUSAHAAN YANG MENERAPKAN ENTERPRISE RISK MANAGEMENT (ERM) - Zaky, Ahmad; Mukaram, Mukaram (Jurnal Riset Bisnis dan Investasi, 2015)
A risk is not an odd thing which is encountered in the business activities. Therefore, risk management is becoming a serious concern within the company. To anticipate the impact of risk on the company and in order to create the Firm Value, Enterprise Risk Management (ERM) has been developed. ERM is not just aimed at the creation of value for the company, ERM is believed to be able to manage the risks facing the company better and integrated through the business organization. However, in 2008, the financial crisis in the United States become consideration of the impact of the implementation of ERM in the firm, particularly in the financial sector. An unsuccessful management of the firms in the financial sector could have a major impact on the economy of a country that resulted in the financial crisis occurred and many of those who argue that this is due to an irrelevant and improper implementation of ERM. In order to examine this, this research conducted on the financial sector in Indonesia, especially the listed banking companies in Indonesia Stock Exchange. In this study, the samples are 37 banking firms listed on Indonesia Stock Exchanges to examining the differences Firm Value means between the banking firms which implement ERM and banking firm which do not implement ERM. The Results show that among the bank companies, there is no significant difference of the magnitude of the Firm Value of an existing company. In essence, the financial sector especially the banking industry in Indonesia, the implementation of ERM is not an appropriate solution of efforts to increase the value of the firm in order to increase the potential growth of the investment.